UNDERGROUND COAL GASIFICATION – POSSIBILITIES IN SLOVENIA - Medved, Milan; Konovšek, Damjan (Journal of Energy Technology, 2024)
Slovenia still has significant amounts of unexploited coal; consequently, this article explores the additional option of using this domestic primary energy source, using the underground coal gasification(UCG) methodology. We described the general recommendations and findings from the UCG tests conducted throughout the world, relating to the testing performed in Velenje. Based on the recommendations and findings of the UCG tests, the descriptions of different technologies and the characteristics of the Velenje coal deposit, we established the most appropriate technology for the gasification of Velenje coal, which is the UCG technology using the ELW method in combination with the modified CRIP method for ignition and underground gasification. The test geometry and the operating parameters for UCG Velenje have been assessed on the basis of the modular gasification scheme of the company Carbon Energy Pty Ltd (CEPL), which was produced in the scope of the testing conducted in Bloodwood Creek, Australia.